Espacialização de informações na gestão de sistemas de abastecimento de água utilizando sistema de informação geográfica - SANTOS, Aline Christian Pimentel Almeida (Universidade Federal do Pará, 2015)
To evaluate the spatial information in the management of Water Supply System (ATS). For this they were defined and adopted to the survey (Phase 1), being divided into data of actual losses, commercial and operating expenses. In Phase 2, the base map of study area and data used were stored and organized in a Geographic Information System (GIS) using ArcGIS 9.3 software, which built the data model for the study, and defined the topology be used for identification of specialized data, building the database and the creation of georeferenced layers. In phase 3 was calculated from water balance in the main units of SAAs studied with certain losses in raw water supply, treatment, on the reservation, and distribution. In phase four indicators were calculated to evaluate the performance of SAAs, including: coverage index, total index of actual loss, loss index in the collection, rate of loss of business, index of energy consumption in SAA, index of energy costs Electric, among others. In phase 5 was proposed to the spatial and GIS presentation of the results obtained in earlier phases. Thus, considering the data adopted, it was possible to identify the values of actual losses and performance indicators in each sector of the SAA studied, being, for example, sector 9, which presented the highest rate of total loss, reaching 59, 10%, followed by sections 4, 8 and 5. The most significant loss for the system was the loss distribution, with 9 industry to a loss of 57% loss on treatment was 3.4% in the third sector, and sectors with the highest loss of adduction weresectors 6 and 8, with 3.5%. The percentage of water unaccounted were higher in sectors 1 and 5. Sectors 1, 3, 4 and 6 are those with the highest energy consumption per volume of water produced. Therefore, the spatial data in GIS facilitated the visualization and data analysis adopted in this research.